2020
DOI: 10.1093/ajcn/nqz347
|View full text |Cite
|
Sign up to set email alerts
|

The autophagic-lysosomal and ubiquitin proteasome systems are simultaneously activated in the skeletal muscle of gastric cancer patients with cachexia

Abstract: Background Cancer cachexia is characterized by weight loss, especially ongoing skeletal muscle loss, and is associated with poor patient outcomes. However, the molecular mechanism of skeletal muscle wasting is not fully understood. Objectives We aimed to investigate muscle fiber morphology and proteolysis system activity changes that may account for cancer cachexia and to relate these changes to patients’ clinical phenotypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 45 publications
3
46
0
1
Order By: Relevance
“…cofilin, dystonin, and vinculin) in pancreatic cancer patients. 50 While a significant reduction in the cross-sectional area of muscle fibres was observed in gastrointestinal cancer patients with cachexia and muscle loss, 46,51 Op den Kamp et al found no such change in cachectic patients with advanced non-small-cell lung cancer compared with pre-cachectic patients. 52 Finally, no significant alteration in fibre typing associated with cancer cachexia has been reported in clinical studies, either of gastrointestinal 51,53 or lung 54 cancer.…”
Section: Structure and Typing Of Muscle Fibresmentioning
confidence: 99%
See 3 more Smart Citations
“…cofilin, dystonin, and vinculin) in pancreatic cancer patients. 50 While a significant reduction in the cross-sectional area of muscle fibres was observed in gastrointestinal cancer patients with cachexia and muscle loss, 46,51 Op den Kamp et al found no such change in cachectic patients with advanced non-small-cell lung cancer compared with pre-cachectic patients. 52 Finally, no significant alteration in fibre typing associated with cancer cachexia has been reported in clinical studies, either of gastrointestinal 51,53 or lung 54 cancer.…”
Section: Structure and Typing Of Muscle Fibresmentioning
confidence: 99%
“…45 Skeletal muscle ultrastructure also appears to be impaired, with an apparent disorganization and autophagosome formation in gastric cancer patients with cachexia. 46 The protein expression of myosin heavy chains, a major component of the muscular contractile system, was increased (for isoforms 1, 4, and 8), 47 decreased, 48 or unchanged 49 in cachectic patients with gastrointestinal cancer. Other muscular structural components have also been studied.…”
Section: Structure and Typing Of Muscle Fibresmentioning
confidence: 99%
See 2 more Smart Citations
“…As a fatal, polyfactorial, and irreversible syndrome, cachexia affects about 50-80% of patients with various types of tumors [3] . Cancer cachexia has been defined by an international consensus as a multifactorial syndrome including loss of weight, muscle atrophy, weakness, anorexia, fatigue, low immunity and severe hematopoietic abnormalities [4][5][6][7] . It is well accepted to concentrates on cachexia as a metabolic disorder.…”
Section: Introductionmentioning
confidence: 99%